Factors that Affect the Level of Customer Satisfaction and Repurchase Intention on Tokopedia - Komara, Edi; Fathurahman, Fajar (Research of Business and Management, 2024)
This study investigates the roles of various factors such as Customer Service, Shipping, Tracking, Returns, Sales Promotion, Customer Satisfaction, and Repurchase Intention within the Tokopedia E-Commerce application. Data collection took place over a week, from July 13 to July 20, 2023, with a sample size of 144 respondents. The research employed a descriptive research design and gathered empirical data through online surveys. Structural Equation Modeling was utilized to analyze the data and test several hypotheses. Findings indicate that Customer Service and Tracking do not significantly impact Customer Satisfaction, whereas Shipping, Returns, and Sales Promotion positively influence Customer Satisfaction. Additionally, Customer Satisfaction positively affects Repurchase Intention. The managerial implication suggests that optimizing Customer Service and Tracking could enhance Repurchase Intention. Future research may explore different samples and incorporate additional variables.